Structural performance of masonry elements : mortar coating layers influence /: mortar coating layers influence. ([2019]) - Delgado, João M. P. Q; Guimarães, Ana Sofia; Azevedo, António C; Oliveira, Romilde A; Silva, Fernando A. N; Sobrinho, Carlos W. A. P
No abstract available